Dilatation and Dysfunction of the Right Ventricle Immediately After Ultraendurance Exercise: Exploratory Insights From Conventional Two-Dimensional and Speckle Tracking Echocardiography - Oxborough, David; Shave, Robert; Warburton, Darren; Williams, Karen; Oxborough, Adele; Charlesworth, Sarah; Foulds, Heather; Hoffman, Martin D.; Birch, Karen; George, Keith (Circulation. Cardiovascular imaging, 2011)
Running an ultramarathon has been shown to have a transient negative effect on right ventricular (RV) and left ventricular (LV) function. Additionally, recent findings suggested that ultraendurance athletes may be more at risk of developing a RV cardiomyopathy. The standard echocardiographic assessment of RV function is problematic; however, the introduction of ultrasonic speckle tracking technology has the potential to yield a comprehensive evaluation of RV longitudinal function, providing new insights into this phenomenon. Thus, the primary aim of this exploratory study was to evaluate comprehensively RV structure and function after a 161-km ultramarathon and establish whether changes in the RV are associated with alterations in LV function. Myocardial speckle tracking echocardiograms of the RV and LV were obtained before and immediately after a 161-km ultramarathon in 16 healthy adults. Standard echocardiography was used to determine RV size and function and LV eccentricity index. Speckle tracking was used to determine the temporal evaluation of indices of RV and LV function. RV size was significantly increased postrace (RV outflow, 32 to 35 mm, P=0.002; RV inflow, 42 to 45 mm, P=0.027) with an increase in LV eccentricity index (1.03 to 1.13, P=0.006). RV strain (ε) was significantly reduced postrace (-27% to -24%, P=0.004), but there was no change in the rates of ε. Peak ε in all planes of LV motion were reduced postrace (longitudinal, -18.3 to -16.3%, P=0.012; circumferential, -20.2% to -15.7%, P=0.001; radial, 53.4% to 40.3%, P=0.009). Changes in RV size and function correlated with diastolic strain rates in the LV. This exploratory study demonstrates RV dilatation and reduction in function after an ultramarathon. Further research is warranted to elucidate the mechanisms responsible for these findings. It is not clear what clinical impact might result from consecutive bouts of postexercise RV dysfunction.